Mental health and pain : somatic and psychiatric components of pain in mental health - Marchand, Serge; Saravane, Djea; Gaumond, Isabelle; Marchand, Serge (Springer Paris, 2014)
This book proposes a didactic approach to the different aspects of pain in mental health. The various chapters cover the myths, neurophysiology, perception, measurement and management of pain in mental health. The most common problems, including mood disorders, schizophrenia, anxiety, somatoform disorders, and pervasive developmental disorders, are covered. Each chapter addresses the problem of pain by putting an emphasis on the characteristics of different populations of patients suffering from mental illness. The book helps specialists working in different areas of mental health to appreciate the importance of pain problems in mental health, and also offers avenues for the measurement and treatment of pain in these patients. Mental health and pain are complex issues. They also share certain mutually influential neurophysiological mechanisms, which makes it even more difficult to identify their specific individual characteristics. This duality between the somatic and psychic components can become a pitfall for the specialist in mental health since it can be difficult to disentangle the evolution of a painful condition from the mental illness.